Indian english poetry and fiction - Gopal, N R, Ed; Sachar, S, Ed (Atlantic, 2018)
The essays in the Volume are by very established as well as up-coming scholars and the readers will realise the substantial values of the insights that the pieces contain. Most anthologies published carry a great load of articles on fiction writers who often are already familiar and researched. This anthology strikes a balance between poetry and fiction. It focuses upon relatively unknown poets whose poetry merits serious consideration for reason either of stylistic parameters or of thematological nemesis. Essays on poetry carry comparative, historical and formalistic approaches in relation to distinguished poets like Rabindranath Tagore, Nissim Ezekiel and Vikram Seth. The editor's interview with Charu Sheel Singh is added to bring variety and focus of perspective to what a creative writer feels about literature in question.